Effects of individualized dietary counseling on nutritional status and quality of life in post-discharge patients after surgery for gastric cancer: A randomized clinical trial - Yan, Hongxia; He, Fang; Wei, Jianjian; Zhang, Qiuxiang; Guo, Chunguang; Ni, Jinnv; Yang, Fangyu; Chen, Yingtai (Frontiers in Oncology, 2023)
Background: Currently, the supporting evidence for dietary counselling is insufficient. The aim of this study was to evaluate the impact of individualized dietary counselling on nutritional outcomes and quality of life (QOL) in patients undergoing surgery for gastric cancer. Methods: This study was a prospective, single-center, randomized controlled trial. The patients after surgery for gastric cancer were randomly assigned (1:1) to intervention group and control group. In the intervention group, patients receive individualized dietary counselling based on individual caloric needs and symptom assessment at 24 hours before discharge, 14, 21, 30 and 60 days postoperatively. Patients in the control group received routine dietary counselling. The primary endpoint was body mass index (BMI) loss at 30, 60 and 90 days after surgery, the secondary endpoints were caloric and protein intake at 30 and 60 days after surgery, blood parameters, the 90-day readmission rate, and QOL at 90 days after surgery. Results: 130 patients were enrolled; 67 patients were assigned to the intervention group and 63 to the control group. At 60 days after surgery, caloric goals were reached in 35 patients (77.8%) in the intervention group, and 14 patients (40.0%) in the control group (P=0.001), protein goals were reached in 40 patients (88.9%) in the intervention group, and 17 patients (48.6%) in the control group (P<0.001). Compared with the control group, patients in the intervention group were significantly less BMI loss at 30 days (-0.84±0.65 VS -1.29±0.83), 60 days (-1.29±0.92 VS -1.77±1.13) and 90 days (-1.37±1.05 VS -1.92±1.66) after surgery (all P<0.05). Subgroups analysis by surgery type showed that the intervention could significantly reduce BMI loss in patients undergoing total and proximal gastrectomy at 30 days (-0.75±0.47 VS -1.55±1.10), 60 days (-1.59±1.02 VS -2.55±1.16) and 90 days (-1.44±1.19 VS -3.26±1.46) after surgery (all P<0.05). Regarding the QOL at 90 days after surgery, the patients in the intervention group had significantly lower level of fatigue, shortness of breath and stomach pain, better physical function and cognitive function (P<0.05). Conclusions: Post-discharge individualized dietary counselling is an effective intervention to reduce post-gastrectomy patient weight loss, and elevate caloric intake, protein intake and QOL.